2000
DOI: 10.3354/meps195117
|View full text |Cite
|
Sign up to set email alerts
|

Damage and recovery of Photosystem II during a manipulative field experiment on solar bleaching in the coral Goniastrea aspera

Abstract: The solar radiation regime on differently oriented surfaces of the shallow-water coral Goniastrea aspera is markedly different Field experiments involving rotation of small (20 cm diameter) hemispherical colonies exposed hitherto protected surfaces of the colonies to high levels of photosynthetically active radiation (PAR) whilst reducing PAR on the opposite surface. Photodamage and recovery, respectively, were recorded in the symbiotic algae using non-invasive chlorophyll fluorescence techniques. Measurements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 13 publications
5
46
0
Order By: Relevance
“…These two phenomena are diagnostic of an energetically uncoupled system in which the transmembrane proton gradient, established by the photochemical reactions in the functional reaction centers, is dissipated without generating ATP (23). This fluorescence kinetic pattern, uniquely found in thermally sensitive zooxanthellae, qualitatively differs from photoinhibition (24)(25)(26), with which the time constant for electron transfer increases as the reaction centers become increasingly impaired (27). Moreover, in thermally sensitive clones of zooxanthellae, the pattern of change in photochemical energy conversion occurs over a very narrow thermal window of Ͻ2°C.…”
Section: Resultsmentioning
confidence: 97%
“…These two phenomena are diagnostic of an energetically uncoupled system in which the transmembrane proton gradient, established by the photochemical reactions in the functional reaction centers, is dissipated without generating ATP (23). This fluorescence kinetic pattern, uniquely found in thermally sensitive zooxanthellae, qualitatively differs from photoinhibition (24)(25)(26), with which the time constant for electron transfer increases as the reaction centers become increasingly impaired (27). Moreover, in thermally sensitive clones of zooxanthellae, the pattern of change in photochemical energy conversion occurs over a very narrow thermal window of Ͻ2°C.…”
Section: Resultsmentioning
confidence: 97%
“…Although the depletion of pigmentation also occurred at elevated temperature in the absence of DFB, as reported in other experimental studies of coral bleaching, iron limitation exacerbated the effect and caused substantial increases in DT/(DD + DT) at high temperature. In corals this increase in the conversion of DD to the photoprotective deepoxidated form, DT (Ambarsari et al 1997;Brown et al 1999;Warner and Berry-Lowe 2006), results in higher quenching of singlet chlorophyll by NPQ in the algae, typically to avert photo-oxidative damage (Casper-Lindley and Bjö rkman 1998).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, focus has shifted toward understanding the plasticity of thermal tolerance in corals, and numerous studies have identified a direct link between thermal preconditioning and bleaching susceptibility from both field observations (Castillo and Helmuth, 2005;Maynard et al, 2008;Thompson and van Woesik, 2009;Castillo et al, 2012;Shuail et al, 2016) and experimental manipulation (Brown et al, 2000(Brown et al, , 2002Dove et al, 2006;Middlebrook et al, 2008;Bellantuono et al, 2012b;Bay and Palumbi, 2015). For example, Acropora, Pocillopora, and Porites from the Great Barrier Reef showed lower rates of bleaching during the 2002 bleaching event than the 1998 event, despite more intense conditions during the 2002 event (Maynard et al, 2008).…”
Section: Thermal History and Bleaching Susceptibilitymentioning
confidence: 99%